1960
DOI: 10.1002/zaac.19603050103
|View full text |Cite
|
Sign up to set email alerts
|

Beiträge zur Komplexchemie der Phosphine und Phosphinoxyde. VII. Schwermetallkomplexe des Diphenylphosphins

Abstract: Aus wasserfreiem CoBr2 und (C6H5)2PH entstehen in absolutem Methanol nacheinander drei verschiedene Komplexverbindungen. Das sich zuerst bildende [{(C6H5)2PH}3CoBr2] liegt in Benzol monomer vor und besitzt Nichtelektrolytcharakter. Das magnetische Moment von 2,01 BM spricht deutlich für einen trigonal‐bipyramidalen Bau des Komplexes. Des weiteren kann ein isomerer Komplex der Zusammensetzung [{(C6H5)2PH}3CoBr]Br isoliert werden, der eine Leitfähigkeit im Ausmaß eines binären Elektrolyten aufweist. Das magnetis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1962
1962
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Phosphanido‐bridged complexes of transition metals have a history of almost 50 years: the first member of this series, reported in 1960, is the dimeric palladium(II) complex [Pd(Cl)(μ‐PPh 2 )(PPh 2 H)] 2 ,2 which was at that time not recognised as a phosphanido‐bridged complex 3. In the following years, a lively research led to the synthesis and characterisation of hundreds of new polynuclear compounds characterised by one or more phosphanido groups bridging two (or more) metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphanido‐bridged complexes of transition metals have a history of almost 50 years: the first member of this series, reported in 1960, is the dimeric palladium(II) complex [Pd(Cl)(μ‐PPh 2 )(PPh 2 H)] 2 ,2 which was at that time not recognised as a phosphanido‐bridged complex 3. In the following years, a lively research led to the synthesis and characterisation of hundreds of new polynuclear compounds characterised by one or more phosphanido groups bridging two (or more) metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…These are reported in Error estimated in value determined from frozen solutions ±0.009. 6 (g) = 1/8(g| | + 2g±). c (g) read directly from solution esr spectra at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper we report the results of our esr studies of the low-spin complexes Co[(CH3)2NPF2]8X2, Co-{[(CH8)2N ]2PF} 8X2, and Co(Ph2PH)8Br2. The last complex, whose preparation was reported by Issleib and Wenschul,6 is included in this study because it has been shown by a single-crystal X-ray diffraction study to be a five-coordinate complex, the structure of which lies intermediate between a square pyramid and trigonal bipyramid. 7 We suggest that the unpaired electron orbital of the complexes consists of predominantly 3d,z character plus a small amount of s character.…”
mentioning
confidence: 99%
“…it was originally believed to be. 13 In contrast to the numerous3 studies of oxidative addition reactions of zerovalent palladium and platinum complexes, few studies have been conducted with nickel complexes though oxidative additions are implicated in numerous catalytic reactions involving nickel species. 14 The limited number of studies is probably due to the general extreme air sensitivity or lack of reactivity of these species.…”
Section: Methodsmentioning
confidence: 99%